Lily and the paper man - Upjohn, Rebecca, 1962- (Second Story Press, 2007)
At first, Lily is afraid of the paper man whom she sees on the way home from school, but when winter comes and she sees that he has no warm clothes, she tells her mother and father that she has an idea.